Usher and Schumpeter on Invention, Innovation and Technological Change: Comment - Schweitzer, Paul R. (Quarterly Journal of Economics, 1961)
Journal Article Usher and Schumpeter on Invention, Innovation and Technological Change: Comment Get access Paul R. Schweitzer Paul R. Schweitzer Department of Labour, Ottawa Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 1, February 1961, Pages 152–154, https://doi.org/10.2307/1883211 Published: 01 February 1961